Mapping metabolome changes in Luffa aegyptiaca Mill fruits at different maturation stages via MS-based metabolomics and chemometrics - Maamoun, Amal A. (J Adv Res, 2019)
INTRODUCTION: Luffa aegyptiaca Mill, sponge gourd or Egyptian cucumber, is grown worldwide for its edible fruit consumed as a vegetable like cucumber. Unlike young fruit (YF), the fully mature ripened fruit (MF) is strongly fibrous and is used as a cleanser to make scrubbing bath sponges. YF undergoes a complex series of physiological and biochemical changes during fruit ripening. However, the chemical compositional differences between YF and MF in Luffa aegyptiaca have not been distinguished to date. OBJECTIVES: Comprehensively compare the metabolites profile of YF and MF to give insight on how maturation stage affects chemical composition. METHODS: Mass-based metabolomics comprising GC/MS and UHPLC/MS were adopted in this study targeting its volatile and non-volatile metabolites coupled with chemometrics to rationalize for the differences. RESULTS: A total of 53 volatile metabolites were identified via headspace solid phase microextraction (SPME) comprising 66.2% aldehydes/furans, 51.6% alcohols, 38.2% ketones, 15.1% acids and 10.1% aromatics of which aldehydes/ furans were dominant at both fruit stages. Young fruit was in general more erniched in metabolites as revealed from UHPLC/MS and GC/MS analyses. The YF group encompassed higher levels of short chain alcohols (1-octen-3-ol) and aldehydes ((E)-2-hexenal and cucumber aldehyde) in addition to terpenoids (linalool). In contrast, fatty acids (octanoic acid) predominated MF specimens. UHPLC/MS analysis revealed for several oleanene triterpene glycosides as major secondary bioactive compounds, dihydroxy-oxo-oleanenoic acid glycoside found more abundant in YF versus MF as revealed from multivariate data analyses. CONCLUSIONS: Our results reveal for the distinct metabolite changes in L. aegyptiaca fruit in its different stages and to rationalize for its different usage.